IDENTIFIKASI STRUKTUR GEOLOGI BERDASARKAN ASPEK MORFOLOGI, STRATIGRAFI, POLA JURUS LAPISAN BATUAN DAN SEBARAN BATUAN : STUDI KASUS DAERAH BANTARUJEG-MAJALENGKA, PROVINSI JAWA BARAT - Haryanto, Iyan; -, Nurdradjat; Saputra, Irdanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
The study is located at Bantarujeg, Majalengka, West Java where tertiary sedimentary rocks are exposed. The depositional environment is concluded as shallow marine – deep water. In a present day, the sedimentary rocks are deformed and create a steep hills extending from west – east of the study area as a result of fault and folding processes. In some of the study area, deformed sedimentary rocks feature is resulted by sedimentation processes called slump. Various deformation model and interpretation on study area is often confuse geological history interpretation of study area. The main cause of folding in the study area may be adjacent to sedmentation processes or tectonic processes.The study is based on structural interpretation on topography map, drainage pattern, and digital elevation model analysis (DEM). Field observation is conducted to measure structural feature and identify sedimentology and morphology aspects.Structural geology Bantarujeg is expressed by steep hills morphology extending from west – east. The morphology is controlled by rock strike with rock dip measured from 30o-60o. In the middle of the depression (valley), layer dip generally above 40o shows the area is a result of compression and related to reverse fault. Local fold and drag fold is also founded on the reverse fault zone and in other location slump structure and local drag fold also identified. In general, the study area is a result of compression tectonic regime creating fold and thrust belt followed by tear fault deformation.